Central bank intervention and bank liquidity: Evidence from the paycheck protection program - Arora, Parush; Tran, Derek (Journal of Banking & Finance, 2025)
This paper explores the role of monetary systems when fiscal policy is implemented through the financial sector during a liquidity shock. We use loan-level transactions from the Paycheck Protection Program (PPP) to understand how a bank’s decision to borrow funds from the discount window (DW) affected its lending behavior during the COVID-19 crisis. Using an instrumental variable approach, we find a causal relationship between DW access/borrowing and the number of PPP loans extended by large banks, indicating that access to DW increased the effectiveness of the PPP. Although both large and small banks accessed the DW in the absence of a long-term funding source, accessing the DW almost doubled the PPP lending for large banks, but did not have a statistically significant effect for smaller banks. However, during the period without long-term funding, the DW played an important role in relaxing liquidity constraints for large banks and increasing the overall efficiency of the PPP. Beyond PPP loans, we find that DW access led banks to increase their non-PPP lending by 70% relative to their reserves, suggesting broader benefits to credit provision. The DW effect on PPP lending disappeared after the introduction of PPP Lending Facility as the banks substituted towards the long-term funding, however its impact on non-PPP lending remained significant in both phases.